2016
DOI: 10.1186/s13104-016-1963-0
|View full text |Cite
|
Sign up to set email alerts
|

Survival after severe amitriptyline poisoning with prolonged ventricular tachycardia and cardiac arrest

Abstract: BackgroundTricyclic antidepressants (TCA) are becoming one of the most frequently used substances in self poisoning. Significant morbidity and mortality associated with TCA overdose are often related to and refractory hypotension. We report the first case of survival after severe amitriptyline poisoning, leading to prolonged cardiac arrest and ventricular tachycardia (VT), resuscitated with 3 h of uninterrupted cardiac massage and Direct current (DC) shocks.Case presentationA 25 year old girl presented with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…The predicted mean QTcB in the study mimicking that described by Paksu et al [ 12 ] was 512 ms (488 ms observed in the clinic). In case of a virtual 25-year-old female with TdP described by Abeyaratne et al [ 52 ], the arrhythmia was simulated in two out of ten virtual patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The predicted mean QTcB in the study mimicking that described by Paksu et al [ 12 ] was 512 ms (488 ms observed in the clinic). In case of a virtual 25-year-old female with TdP described by Abeyaratne et al [ 52 ], the arrhythmia was simulated in two out of ten virtual patients.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the severity of clinical findings of AT intoxication is weakly correlated with AT serum levels [ 12 ]. Abeyaratne et al [ 52 ] described the case of 25-year old female intoxicated with ca. 500 mg of AT who developed TdP arrhythmia 2 h after poisoning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erken risk sınıflaması bu riski azaltabilir. TA zehirlenmelerinde, sebep çoğunlukla ventriküler aritmilerdir ve kardiopulmoner resüsitasyon süresini uzatmak mortalite oranını azaltabilmektedir (16).…”
Section: Bulgularunclassified